Experimental study on the mixed refrigerant heat transfer performance in a plate-fin heat exchanger during a single-stage cryogenic cycle. (25th January 2016) - Cao, Le; Liu, Jinping; Li, Rixin; Huang, Shizhe; Zhang, Fayong; Xu, Xiongwen
Highlights: A cryogenic mixed refrigerant J-T cycle employing a plate-fin heat exchanger was established. Heat transfer performance of mixed refrigerant in recuperative heat exchanger was discussed. 5 condensation correlations and 13 flow boiling correlations were selected to analyze the overall HTCs. Some suggestions about plate-fin heat exchanger design were proposed. Abstract: Plate-fin heat exchangers (PFHEs) are mostly employed in small- and medium-sized LNG plants. However, studies on the heat transfer performance of mixed refrigerant in a PFHE under low-quality have rarely been conducted. In this paper, an experimental setup that utilized a single-stage cryogenic cycle with commercial compressors and a customized PFHE was established to study the heat transfer performance of the PFHE throughout the cool-down process. The components of the mixed refrigerant included nitrogen, methane, ethylene, propane and isobutane. Several experiments were conducted to obtain a refrigeration temperature as low as −160 °C. The characteristics of the cool-down process and the temperature difference change in the RHE were discussed. Meanwhile, five sets of condensation correlations and 13 sets of flow boiling correlations were selected to predict the HTC in the PFHE. The experimental overall HTC of the PFHE based on the hot sides was approximately between 11.88 and 37.74 W m −2 K −1 . However, most of the existing correlations were not able to correctly predict the HTC of the PFHE in this work. Meanwhile, some suggestions regarding the PFHE design in a mixed refrigerant cryogenic system were proposed.